White Matter Microstructural Changes and Episodic Memory Disturbances in Late-Onset Bipolar Disorder - Alves, Gilberto Sousa; Knöchel, Christian; Paulitsch, Michael Anton; Reinke, Britta; Carvalho, André F.; Feddern, Richard; Prvulovic, David; Sudo, Felipe Kenji; Pantel, Johannes; Reif, Andreas; Oertel, Viola (Frontiers in Psychiatry, 2018)
Background: Bipolar disorder (BD) has been associated with distributed network disruption, but little is known on how different clinical subtypes, particularly those with an earlier and later onset of disease, are related to connectivity changes in white matter (WM) tracts. Methods: Diffusion tensor imaging (DTI) and volumetric measures were carried out in early-onset bipolar patients [(EOD)(n=16)], late-onset bipolar disorder [(LOD)(n=14)] and healthy controls (n=32). We also computed ROI analysis of grey matter (GM) and white matter (WM) volumes using the regions with significant group differences in the DTI parameters. Cognitive and behavior measurements were analyzed between groups. Results: Lower fraction of anisotropy (FA) in the right hemisphere comprising anterior thalamic radiation, fornix, posterior cingulate, internal capsule, splenium of corpus callosum was observed in the LOD in comparison with EOD; additionally, lower FA was also found in the LOD in comparison with healthy controls, mostly in the right hemisphere and comprising fibers of the splenium of the corpus callosum, cingulum, superior frontal gyrus and posterior thalamic radiation; LOD also showed worse episodic memory performance than EOD; no statistical significant differences between mood symptoms, WM and GM volumes were found between BD groups. Conclusion: Even after correcting for age differences, LOD was associated with more extensive WM microstructural changes and worse episodic memory performance than EOD; these findings suggest that changes in the WM fiber integrity may be associated with a later presentation of BD, possibly due to mechanisms other than neuroprogression. However, these findings deserve replication in larger, prospective, studies.